MENINGKATKAN PEMAHAMAN MAJAS DALAM PUISI MENGGUNAKAN POWERPOINT INTERAKTIF PADA KELAS 4 SDN CIPEUNDEUY. - Chintia; Djuanda, Dadan; Ahmad Syahid, Aah (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2024)
ENHANCING THE COMPREHENSION OF POETRY'S PACE BY UTILIZING INTERACTIVE POWERPOINT IN THE FOURTH-GRADE CLASS OF SDN CIPEUNDEUY. The research entitled "Enhancing The Comprehension Of Poetry's Pace By Utilizing Interactive Powerpoint In The Fourth-Grade Class Of SDN Cipeundeuy" is a study conducted at SDN Cipeundeuy with 21 fourth-grade students as research subjects. The purpose of this research is to improve the understanding of figures of speech among fourth-grade students by using interactive powerpoint as a learning media to facilitate and increase students' enthusiasm in learning figures of speech. This research was carried out based on the initial data found by the researcher that students still have difficulty in understanding poetry that has figurative language in its verses. Thus, this research was conducted to help students understand figures of speech more deeply. The research method used in this study was a qualitative method with a classroom action research technique using the Kemmis Mc. Taggart model. The findings obtained by the researcher during the research activities include an improvement in the understanding of figures of speech among students. The average pre-test score was 26 out of 21 students, with the lowest score being 20 and the highest score being 50. In the first cycle, the average post-test score of the students showed an improvement to 64, with the lowest score being 50 and the highest score being 80. In the second cycle, the students showed improvement again, with the average score increasing to 85, with the lowest score being 70 and the highest score being 100. Keywords : Poetry Learning, Figures of Speech Learning, Powerpoint Media.